Evaluation of preoperative predictive factors for difficult laparoscopic cholecystectomy - Elgammal, Ahmed S.; Elmeligi, Mohamed H.; Koura, Mostafa M. Abo (International Surgery Journal, 2019)
Background: Laparoscopic cholecystectomy is the gold standard treatment for symptomatic cholelithiasis. However, of all Laparoscopic cholecystectomies, 1-13% requires conversion to an open surgery. Thus, for surgeons it would be helpful to establish criteria that would predict difficult laparoscopic cholecystectomy and conversion preoperatively. The objective of the study was to assess preoperative parameters for predicting the difficult laparoscopic cholecystectomy and its conversion. Methods: Prospective study includes 100 patients having symptomatic cholelithiasis. All patients underwent elective LC in Department of General Surgery in Menoufia University Hospital and Tala General Hospital. The collected data of preoperative factors include sex, age, previous attack, history of ERCP, obstructive jaundice, obesity (BMI), lower abdominal scar, palpable gallbladder, wall thickness of, number of stones, size of stones and impacted stone. Difficulty levels according to intraoperative parameters were easy (0–5), difficult (6–10), and conversion from laparoscopic to open surgery. Results: In this study, previous history of attacks of cholecystitis (p=0.001) and wall thickness (p=0.007) were found to be statistically significant in predicting difficult LC in both univariate and multivariate analyses. Other factors such as age (p=0.002), BMI greater than 27.5 (p=0.02), palpable GB (p=0.003), impacted stone (p=0.01) were found to be statistically significant in predicting difficult LC. Factors such as sex, and abdominal scar were not statistically significant in predicting difficult LC. Conclusions: The difficult laparoscopic cholecystectomy and conversion to open surgery can be predicted preoperatively based on number of previous attacks of cholecystitis, WBC count, Gall bladder wall thickness and size of stones.